2021
DOI: 10.1029/2021ea001744
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Parameterization Schemes in Capturing the Characteristics of Extratropical Cyclones Over the South Pacific Ocean

Abstract: The extratropical cyclone (ETC) of August 2015 in central Chile was investigated using the WRF model to analyze the sensitivity of meteorological variables to different physical parameterization schemes. This study assesses the performance of different physical schemes in the simulation of track, core pressure, mean sea level pressure, wind direction and wind speed associated with ETC over the South Pacific. The analysis uses a total of 36 sensitivity experiments, consisting of: two microphysics schemes; three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, this study also quantified the relationship between intense northerly wind events and the passage of cyclones over the area. Although the relation between these two phenomena has been extensively studied (Barrett et al, 2011;Befort et al, 2019;Bitencourt et al, 2011;Domingues et al, 2019;Gómez et al, 2021;Ulbrich et al, 2009;Viale and Nuñez, 2011), this research identified extratropical cyclones as the primary atmospheric phenomenon responsible for extreme northerly winds in the region.…”
Section: Extratropical Cyclones Over Central Chilementioning
confidence: 99%
“…Furthermore, this study also quantified the relationship between intense northerly wind events and the passage of cyclones over the area. Although the relation between these two phenomena has been extensively studied (Barrett et al, 2011;Befort et al, 2019;Bitencourt et al, 2011;Domingues et al, 2019;Gómez et al, 2021;Ulbrich et al, 2009;Viale and Nuñez, 2011), this research identified extratropical cyclones as the primary atmospheric phenomenon responsible for extreme northerly winds in the region.…”
Section: Extratropical Cyclones Over Central Chilementioning
confidence: 99%